Profil Pemahaman Konsep Siswa pada Materi Sistem Persamaan Linier Tiga Variabel Ditinjau dari Gaya Kognitif - Didik Suliswanto; Dwi Juniati; Pradnyo Wijayanti (Didaktik Matematika, 2020)
Understanding of the concept is needed in studying mathematics, including the topic of the Three Variable Linear Equation System (SPLTV). In fact, there are still many students who don't understand the basic concepts well. The research subjects were students in grade 10 high school, each consisting of one student with field independent and field dependent cognitive style. The research instrument which were used consisted of a concept understanding test and interview guidelines. Data analysis was done through data reduction procedures, data exposure, and making conclusions. The resulting research showed that the field independent students understanding to the concept of SPLTV, namely students stated that the meaning of SPLTV used their own language without being stuck with the notation from SPLTV and students gave examples and non-examples of SPLTV. In addition, in solving problems students are able to use the SPLTV concept well. As the results of the research, the students' understanding of field dependent on the concept of SPLTV is that students explained that the notion of SPLTV was still stuck with the notation of the existing SPLTV and students give examples and non-examples of SPLTV. Moreover, in solving problems, students are less able to use the SPLTV concept well.